Vertical Ascent: A Comprehensive Review of High-Rise Building Development in Raipur (International Journal of Food and Nutritional Sciences, 2022)
This review paper explores the evolution and current state of high-rise buildings in Raipur, shedding light on the architectural, structural, and urban planning aspects that have shaped the city's skyline. From historical landmarks to contemporary marvels, the paper delves into the factors influencing the rise of tall structures, the challenges faced, and the innovative solutions employed in the pursuit of sustainable vertical development. By examining the unique characteristics of high-rises in Raipur, this paper aims to contribute valuable insights into the urbanization trends, engineering advancements, and future prospects for vertical growth in the city.